PREDIKSI FINANCIAL DISTRESS DENGAN RASIO ARUS KAS - Yolanda Puspita Sari; Mudji Utami (Journal of Management and Business, 2009)
This research examine financial ratio of cash flow to predict financial distress. This research argues cash flow ratios have an effect on financial distress condition especially for Indonesian firm. There are 13 cash flow ratios from 17 listed manufacturing firms in Indonesia Stock Exchange (IDX). Period of analysis is 1999-2005. The classification of financial distress firm based on Almilia (2006) that divide firm which financial distress has a negative net income and net equity for 2 years consecutively. This research uses logistic regression to conclude the predictability power of research model. Result shows cash flow ratios have a significance affect on financial distress, such ratios are CFFOTA, CFFOS, IPPEPPE, CHWCTU, RPPETS, DITS and NetdebtTS.